(untitled) (Research, Society and Development, 2021)
The objective of this study was to evaluate the effects of different doses of chicken litter on the SPAD chlorophyll index (Development of Plant and Soil Analysis) and on the dry matter yield (DM) of forage cultivars (cvs.) Of Brachiaria brizantha Marandu, BRS Paiaguás and Xaraés. The experiment was carried out in plastic pots filled with 25 L, in the open air. The experimental design was randomized blocks, with three replications, in a 4x3x6 factorial scheme. Therefore, four doses of organic fertilization (without fertilization - natural soil, 5 t ha-1, 10 t ha-1; and 15 t ha-1 of chicken litter); three cvs. by Urochloa brizantha: (Marandu, BRS Paiaguás and Xaraés); and six evaluation periods (86, 114, 142, 198, 254 and 282 days after the emergence of cultivars). The SPAD indices and DM productivity were evaluated in six consecutive seasons, whose DM was estimated by cutting the forage at a height of 0,20 m from the ground. The increase in the dose of chicken litter increased the productivity of DM, and the SPAD indices of the cultivars. The chicken litter can be used as an alternative source of fertilization for pastures of tropical climate in regions of the cerrado, due to the expressive increases in the production of forage mass, with the maximum productivity of DM obtained with the dose of 9,8 t ha-1 of chicken bed for cv. Marandu, and 15 t ha-1 of chicken litter for the cvs. BRS Paiaguás and Xaraés.